THE USE OF VISUAL RESPONSE SYMBOL TO IMPROVE STUDENTSâ SPEAKING FLUENCY IN SUMMARIZING READING TEXTS OF INTERMEDIATE 3 CLASS IN LB LIA PALEMBANG - RUSMIANA, RATY (Sriwijaya University Learning and Education International Conference, 2016)
to make and share meaning about reading text through the creation of visualrepresentations. This interpretative strategy, known as " visual response symbol,"involves learners in creating symbols, pictures, and other non-linguistic signs tosignify ideas generated through reading. The focus of the study was to investigate ifvisual response symbols technique could improve studentsâ fluency in summarizingreading texts. The study supports teaching practices that provide opportunities forstudents of all ages to make and share meaning through multiple sign systems. Thesample was 17 students of IN 3 level of LBPP LIA Palembang in term II/2016. Thedata were obtained by means of observation, teaching journals and video recordings.Based on the result of the data analysis, it was found out that there was a significantdifference of studentsâ fluency in speaking up their summary of the reading textsafter implementing the visual response symbols. It was also found out that thesamples had positive attitude toward the use of visual response symbols. They also,subconsciously, developed their 4Cs (Critical thinking and Problem solving,Communication, Collaboration, Creativity and Innovation) as they should find anystrategy in order to produce words to tell their friend the summary of the readingtexts they have read. Despite its satisfied finding, this class action research should beconsidered a preliminary technique that needs to be furthered by applying methodsthat are more comprehensive in order to promote studentsâ fluency in speaking aswell as develop their 4Cs.